Penggunaan Madu terhadap Perbaikan Kondisi Klinis dalam Proses Penyembuhan Luka pada Pasien Ulkus Diabetikum - Sari, Lia Novita; Dahlia, Debie; Kurnia, Dhika Ayu (Journal of Telenursing (JOTING), 2024)
This study aims to identify the effectiveness of using honey in increasing the clinical improvement of diabetic ulcers in the wound healing process. The method used is a systematic review by searching research journals in databases, namely Embase, Scopus, PubMed and Proquest with the year of publication of the article starting from 2006-2021. Data analysis was carried out by taking relevant articles in this research, totaling 9 articles. The research results showed that the majority, namely 8 articles (89%), proved the effectiveness of honey in the wound healing process. Conclusion: The use of honey in wound care management has been proven to accelerate the healing process, reduce odor, clean wounds, stimulate granulation, and control infection. Keywords: Diabetic Ulcer, Honey, Wound Healing